2022
DOI: 10.3389/fcvm.2022.929466
|View full text |Cite
|
Sign up to set email alerts
|

E-Selectin/AAV2/2 Gene Therapy Alters Angiogenesis and Inflammatory Gene Profiles in Mouse Gangrene Model

Abstract: For patients with chronic limb-threatening ischemia and limited revascularization options, alternate means for therapeutic angiogenesis and limb salvage are needed. E-selectin is a cell adhesion molecule that is critical for inflammation and neovascularization in areas of wound healing and ischemia. Here, we tested the efficacy of modifying ischemic limb tissue by intramuscular administration of E-selectin/AAV2/2 (adeno-associated virus serotype 2/2) to modulate angiogenic and inflammatory responses in a murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Furthermore, when antitumor drugs were applied, gene expression levels were reduced, suggesting a possible role of E-selectin as an oncogene. Targeting E-selectin has emerged as a potential therapeutic strategy for the treatment of cancer [72][73][74]. Several approaches have been developed to target E-selectin, including monoclonal antibodies and small molecule inhibitors and have shown promise in preclinical studies by reducing tumor growth and metastasis [75][76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when antitumor drugs were applied, gene expression levels were reduced, suggesting a possible role of E-selectin as an oncogene. Targeting E-selectin has emerged as a potential therapeutic strategy for the treatment of cancer [72][73][74]. Several approaches have been developed to target E-selectin, including monoclonal antibodies and small molecule inhibitors and have shown promise in preclinical studies by reducing tumor growth and metastasis [75][76][77][78][79].…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model of hindlimb ischemia was utilized as described 23,24 . Briefly, 8- to 10-week-old male and female (50%; 50%) FVB/NJ mice (001800; Jackson Laboratory) underwent femoral artery and vein ligation at proximal and distal sites.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 8- to 10-week-old male and female (50%; 50%) FVB/NJ mice (001800; Jackson Laboratory) underwent femoral artery and vein ligation at proximal and distal sites. Hindlimb ischemia was confirmed by preoperative and immediate postoperative laser Doppler imaging measurements were obtained as described 23–25 . Any mouse that did not demonstrate postoperative perfusion index of 5% or less of preoperative levels were excluded from further analysis in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these are listed in Table 3. For example, Ribieras et al 152 found that intramuscular delivery of AAV2-E-selectin improved limb salvage, reperfusion, and function in a mouse hind limb gangrene model. E-selectin is a cell-adhesion molecule that mediates recruitment of the stem/progenitor cells that promote angiogenesis in ischemic tissue.…”
Section: Emerging Aav-based Therapies For Padmentioning
confidence: 99%